Gambaran Illness Representation pada Remaja Penderita Kanker - Widya, Florence; Ferliana, Jovita Maria (Noetic Psychology, 2012)
AbstrakCancer was stated as one of the most dangerous ill in the world. Patients who suffered cancer have an unique expereince that affecting their psychological,social and emotional aspect as well as the physical aspect.ÃÂ  The aim of this researchÃÂ  was to explore and to describe how teenage patient who suffered cancer dealing with it using illness representation framework. This was a qualitative approach using case study with two subjects who suffered blood and joints cancer. The result showed that subject with good understanding of their illness able to represent his/ her illness well through his/ her hope, spirit and positive thinking. ÃÂ Kata kunci : Illness representation, teenager, cancer.